Using The Booklets "Raka" (Rawat Kaki) In Preventing Diabetic Neuropati In Mataram City - Aan Dwi Sentana; Ni Putu Sumartini; Akhmad Fatoni (Jurnal Kesehatan Prima, 2020)
One complication of Diabetes Mellitus (DM) is diabetic neuropathy and requires ongoing treatment with a Strategy to reduce the risk of complications. Efforts to prevent one of them by doing regular diabetic foot care. Foot care is considered easy and can be done by the patient independently, but has not been fully carried out by the patient. The purpose of this research is to determine the use of a book in the prevention of diabetic neuropathy in the city of Mataram. This research used a quasi-experiment with a pre-test design post-test group design with a control group. The group was divided into two treatment groups of 30 respondents and the control of 30 respondents was divided by drawing and used purposive sampling. Data collected were foot care behavior using the NAFF questionnaire, foot sensation using monofilament, and foot circulation using an ankle-brachial index. Statistical analysis uses paired T-Test, Independent T-Test, Wilcoxon Sign Rank Test, and Mann Whitney Test. The results obtained have a significant effect on the use of Booklet Raka in preventing diabetic neuropathy in the treatment group by carrying out treatment behavior with p = 0,000 while the control group p = 0.091. Significant increase in circulation only in the treatment group with a value of p = 000 the control group p = 0.863. Foot sensation increased significantly only in the treatment group with a value of p= 0.001 the control group p = 0.445. it can be concluded that the use of Booklet Raka is influential and effective in preventing diabetic neuropathy by carrying out foot care behavior, foot circulation, and sensation in diabetics.